1993
DOI: 10.1007/bf00880070
|View full text |Cite
|
Sign up to set email alerts
|

Adriamycin-induced inhibition of melanoma cell invasion is correlated with decreases in tumor cell motility and increases in focal contact formation

Abstract: Tumor cell adhesion to the extracellular matrix (ECM) is closely linked with tumor cell invasion and metastasis. In this study, we demonstrate that low levels of adriamycin, a widely used anticancer drug, can inhibit the invasion of highly metastatic K1735-M2 mouse melanoma cells in vitro through a reconstituted basement membrane extract. Adriamycin-induced inhibition of melanoma cell invasion occurred at levels of the drug (i.e. 1 ng/ml) that did not inhibit tumor cell growth, suggesting that the observed inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…However, some observations suggest that, these agents might influence focal adhesion zone formation (Repesh et al, 1993) as well as phosphorylation of FAK (Repesh et al, 1993;van Nimwegen et al, 2006), p130Cas and paxillin (Beinke et al, 2003). This could explain the anti-metastasis properties of some anti-cancer drugs such as anthracyclines (Repesh et al, 1993). Conversely, as it is suggested by the MDR cell profile, chronic exposure to drugs may result in reduced integrin expression and function with significant consequences on cell adhesion and migration (Duensing et al, 1996;Liang et al, 2001;Kozlova et al, 2004).…”
Section: Impact Of Anti-cancer Agents On Integrin Expression and Funcmentioning
confidence: 85%
See 1 more Smart Citation
“…However, some observations suggest that, these agents might influence focal adhesion zone formation (Repesh et al, 1993) as well as phosphorylation of FAK (Repesh et al, 1993;van Nimwegen et al, 2006), p130Cas and paxillin (Beinke et al, 2003). This could explain the anti-metastasis properties of some anti-cancer drugs such as anthracyclines (Repesh et al, 1993). Conversely, as it is suggested by the MDR cell profile, chronic exposure to drugs may result in reduced integrin expression and function with significant consequences on cell adhesion and migration (Duensing et al, 1996;Liang et al, 2001;Kozlova et al, 2004).…”
Section: Impact Of Anti-cancer Agents On Integrin Expression and Funcmentioning
confidence: 85%
“…However, some observations suggest that, these agents might influence focal adhesion zone formation (Repesh et al, 1993) as well as phosphorylation of FAK (Repesh et al, 1993;van Nimwegen et al, 2006), p130Cas and paxillin (Beinke et al, 2003). This could explain the anti-metastasis properties of some anti-cancer drugs such as anthracyclines (Repesh et al, 1993).…”
Section: Impact Of Anti-cancer Agents On Integrin Expression and Funcmentioning
confidence: 99%
“…However, recent study has shown that Adriamycin at non-cytotoxic concentrations reduced the invasive behavior of human melanoma cell by suppressing collagenase-1 expression [36]. In addition, Adriamycin at low concentrations lower than those used to suppress cell growth, can inhibit invasion and migration of mouse melanoma cell by modulating cell adhesion [37]. All these findings suggested that Adriamycin-induced inhibition of cell invasion and migration was not solely due to the ability of Adriamycin to cause DNA damage, which triggers p53 protein elevations [38].…”
Section: Discussionmentioning
confidence: 99%
“…Sgadari et al (2000) found that paclitaxel promoted regression of Kaposi's sarcoma (KS) lesions in vivo and that it blocked the growth, migration, and invasion of KS cells in vitro. Doxorubicin appears to have an inhibitory effect on invasion (Repesh et al, 1993;Hikawa et al, 2000).Previous studies in this laboratory showed that selection of RPMI 2650, a noninvasive cell line, with the chemotherapeutic agents paclitaxel and melphalan, resulted in multiple drugresistant phenotypes and in the case of melphalan but not paclitaxel, a highly invasive phenotype (Liang et al, 2001). To further investigate the effects of chemotherapeutic drug selection, in particular doxorubicin and paclitaxel, and the effect of these drugs on adhesive, locomotive and invasive phenotypes, paclitaxeland doxorubicin-selected variants of the human breast cell line MDA-MB-435S-F were established.…”
mentioning
confidence: 99%
“…Sgadari et al (2000) found that paclitaxel promoted regression of Kaposi's sarcoma (KS) lesions in vivo and that it blocked the growth, migration, and invasion of KS cells in vitro. Doxorubicin appears to have an inhibitory effect on invasion (Repesh et al, 1993;Hikawa et al, 2000).…”
mentioning
confidence: 99%